The Effect of Low-Skill Immigration Restrictions on US Firms and Workers: Evidence from a Randomized Lottery - Michael A. Clemens; Ethan Gatewood Lewis (Institute of Labor Economics (IZA), 2022)
The U.S. limits work visas for low-skill jobs outside of agriculture, with a binding quota that firms access via a randomized lottery. We evaluate the marginal impact of the quota on firms entering the 2021 H-2B visa lottery using a novel survey and pre-analysis plan. Firms exogenously authorized to employ more immigrants significantly increase production (elasticity +0.16) with no decrease or an increase in U.S. employment (elasticity +0.10, statistically imprecise) across several pre-registered subsamples. The results imply very low substitutability of native for foreign labor in the policy-relevant occupations. Forensic analysis suggests similarly low substitutability of black-market labor.
Keywords: F22; J61; D22; 330; immigration; immigrant; foreign; labor; mobility; skill; manual; high school; college; firms; elasticity; substitution; productivity; rural; urban